1986
DOI: 10.1128/jcm.24.1.41-46.1986
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of enzyme-linked immunosorbent assay for the diagnosis of pulmonary echinococcosis

Abstract: An enzyme-linked immunosorbent assay was done for the detection of immunoglobulin G and M (IgG and IgM) antibodies to Echinococcus granulosus in surgically proved cases of hydatidosis, especially pulmonary hydatidosis, by use of human hydatid cyst fluid antigen and soluble scolex antigen. This assay was compared with the following standardized techniques: the indirect hemagglutination test, the indirect immunofluorescent antibody test, and Casoni's intradermal test. The enzyme-linked immunosorbent assay, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 5 publications
(7 reference statements)
1
27
0
1
Order By: Relevance
“…It is considered to be highly sensitive and specific in detecting anti-Echinococcus antibodies irrespective of the site of cyst localization in similar study by Wattal, et al [37]. Among purified antigens ELISA for IgG was the most sensitive (96.5%) in comparison to our study which showed almost sensitivity of 100% [37]. These results are similar to those obtained by Kaddah, et al [50].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is considered to be highly sensitive and specific in detecting anti-Echinococcus antibodies irrespective of the site of cyst localization in similar study by Wattal, et al [37]. Among purified antigens ELISA for IgG was the most sensitive (96.5%) in comparison to our study which showed almost sensitivity of 100% [37]. These results are similar to those obtained by Kaddah, et al [50].…”
Section: Discussionsupporting
confidence: 91%
“…Among these ELISA for detection of IgG antibodies is most commonly used. It considered being highly sensitive and specific in detecting anti-Echinococcus antibodies irrespective of the site of cyst localization [37]. The only place in the world that has the highest incidence and prevalence of hydatid disease is the Turkana district, due to the unique role that dogs play in the day-to-day life of their human owner her lungs, coughing and chest pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, ever since the beginning of serological diagnosis of hydatidosis, lung cysts have given very low responses (20). Nevertheless, other locations such as the liver offer good or acceptable serological responses (21)(22)(23). In this work the most sensitive test was ELISA AgB from all the patients together, except 2 of 24 with lung locations ( Table 1, Fig.…”
Section: Discussionmentioning
confidence: 77%
“…The state of infection following PAIR or PAIR-PD was determined based on serologic E. granulosus-specific IgG antibody levels using ELISA (Serion ELISA classic Echinococcus IgG, Institut Virion, Serion GmbH, Wirsburg, Ger-many). Serologic test and ELISA results were evaluated as described by Wattal et al 10 Each patient received prophylactic treatment with oral albendazole (10 mg/kg/day) beginning 48 hours prior to PAIR or PAIR-PD and continuing for 3-6 months after PAIR or PAIR-PD.…”
Section: Methodsmentioning
confidence: 99%